GIST and follicular lymphoma in a rare association – unusual intestinal occlusion case-report - Pinto, José (2018)
GISTs are stromal tumors considered to be sporadic. However, more and more studies describe association between these cancer and other tumors. The association of GIST to lymphomas is particularly rare because the molecular pathway in their development has nothing in common. The authors review the issue and report a case of GIST and follicular-lymphoma association based from a clinical history of a man, 79 years old, subjected to laparotomy in March 2013 because of an intra-abdominal mass of unknown etiology that was causing sub-occlusion, with ongoing worsening pain and abdominal discomfort. The histology of the resected tumor mass documented the presence of an association of a high-risk GIST with a follicular lymphoma. GISTs are rare and have sporadic associations to other cancers. This poorly understood connection can hide diagnostic surprises, you should never forget when we address this type of tumor. Therefore GIST’s patients are the clear example that all patients should be well studied preoperatively and followed cautiously postoperatively.